The development of cell pattern in the root epidermis. - Dolan, L; Roberts, K (1995)
The root epidermis of most angiosperms is composed of a patterned array of hair and non-hair cells. Hair cells may develop randomly in any location in the epidermis (type 1), from specialized cells that form as result of an asymmetric cell division in a mother cell (type 2) or cells may be arranged in files of one cell type or the other (type 3). The development of the epidermis in Arabidopsis has been examined in detail and corresponds to type 3 epidermal development. A combination of physiological and genetic observations indicates that ethylene is a positive regulator of root hair differentiation. Differential exposure of epidermal cells to ethylene as a result of the cellular geometry of the root may account for the wild-type epidermal pattern.